2022
DOI: 10.1093/brain/awac407
|View full text |Cite|
|
Sign up to set email alerts
|

Brain-derived tau: a novel blood-based biomarker for Alzheimer’s disease-type neurodegeneration

Abstract: Blood-based biomarkers for amyloid beta and phosphorylated tau show good diagnostic accuracies and agreements with their corresponding CSF and neuroimaging biomarkers in the amyloid/tau/neurodegeneration [A/T/(N)] framework for Alzheimer’s disease. However, the blood-based neurodegeneration marker neurofilament light is not specific to Alzheimer’s disease while total-tau shows lack of correlation with CSF total-tau. Recent studies suggest that blood total-tau originates principally from peripheral, non-brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 71 publications
5
73
0
1
Order By: Relevance
“…CSF tau fragments starting from amino acid 243 are also shown to associate with tau PET, and could thus be a marker of soluble tau aggregates [38]. Furthermore, brain-derived tau, an assay capturing central nervous system tau released into blood, demonstrates specificity to AD and might reflect neurodegeneration due to AD [39].…”
Section: Novel P-tau Biomarkers In Csfmentioning
confidence: 99%
“…CSF tau fragments starting from amino acid 243 are also shown to associate with tau PET, and could thus be a marker of soluble tau aggregates [38]. Furthermore, brain-derived tau, an assay capturing central nervous system tau released into blood, demonstrates specificity to AD and might reflect neurodegeneration due to AD [39].…”
Section: Novel P-tau Biomarkers In Csfmentioning
confidence: 99%
“…For example, it has been found that direct injection of glutamate into rat insula with no other intervention led to IENFD reductions, highlighting the possibility that imbalances in CNS excitatory neurotransmitters may play a role in IENFD ( 32 ). Alternatively, a “top-around” effect in which signaling molecules or factors are released due to CNS injury could secondarily impact peripheral fibers through the bloodstream or other nonneural pathways ( 33–37 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that direct injection of glutamate into rat insula with no other intervention led to IENFD reductions, highlighting the possibility that imbalances in CNS excitatory neurotransmitters may play a role in IENFD [31]. Alternatively, a "top-around" effect in which signaling molecules or factors are released due to CNS injury could secondarily impact peripheral fibers through the bloodstream or other nonneural pathways [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%